Bank profitability and efficiency in Portugal and Spain: A non-linearity approach - Elisabete Duarte Neves; Catarina Alexandra Neves Proença; António Dias (Journal of Risk and Financial Management, 2020)
This paper aims to analyze the determinants of profitability and bank efficiency in the Iberian Peninsula. To achieve the proposed objective, a sample of 66 Portuguese and Spanish banks was analyzed. To test the hypotheses formulated according to the proposed literature review, the panel data methodology was used; specifically, the Generalized Method of Moments (GMM) system model proposed by and the Tobit model. The results point out that the banking performance, measured in terms of profitability and efficiency, in the Iberian Peninsula, is influenced by internal management variables, but also by the macroeconomic environment. More interestingly, and new in the Iberian banking sector literature, the results prove a positive and negative non-linear relationship between bank size and their levels of profitability and efficiency, respectively.
Keywords: 330; bank size; DEA; GMM system; Iberian Peninsula; performance determinants